Volatility in stock market: evidence from india - N, Shunmuga Rajan; N, Rajasekar (Journal of Management and Science, 2013)
Volatility has been one of the most active and successful areas of research in time series econometrics and economic forecasting in recent decades. Volatility is a statistical measure of the dispersion of returns for a given security or market Index. The main objective of the study is to analyze the volatility of Indian stock market. We have taken five oil sector companies from BSE for this study. The sample companies are Bharath Petroleum, Hindustan Petroleum, Indian Oil, ONGC and Reliance Industries. The Study was conducted from January 2007 to December 2012 and we employed Descriptive Model and Unit Root Test and GARCH Model for making the research more effective and we found that there is high volatility during the study period.